A Study on the Relationship Between Physical Activity, Sedentary Behavior, and Sleep Duration in Preschool Children - Zhenya Chang; Zhenya Chang; Wei Lei (Frontiers Media S.A., 2021)
Purpose: Explore the role of physical activity (PA) and sedentary behavior (SB) in the sleep of preschool children.Method: Preschool children (n = 458) from kindergarten were recruited, measures included accelerometer-derived 24 h activity [SB, light physical activity (LPA), moderate-to-vigorous physical activity (MVPA), daytime sleep duration (DSP), and nocturnal sleep duration (NSP)]. A self-made questionnaire was used to supplementary survey on different types of SB. The two-layer chi-square test and the Cochran-Mantel-Haenszel test were used and significance set at p < 0.05.Results: PA is mainly a protective factor for DSP, while SB is mainly a risk factor for NSP of preschool children; Screen-type SB including screen viewing SB and video game SB is a risk factor for NSP, while quiet learning SB have no significant correlation with sleep duration in preschool children; Gender and social economic status are important factors affecting the association of PA, SB, and sleep duration in preschool children.Conclusions: The relationship between sleep duration at different periods and PA and SB of preschool children is different. Future educators need to gradually realize the different factors affecting the sleep of preschool children at different stages, clarify the protective factors and risk factors, in order to improve the sleep duration of preschool children.